Housework Time from Middle Childhood through Adolescence: Links to Parental Work Hours and Youth Adjustment - Lam, Chun Bun (Dev Psychol, 2016)
The developmental course, family correlates, and adjustment implications of youth housework participation from age 8–18 were examined. Mothers, fathers, and two siblings from 201 European American families provided questionnaire and/or daily diary data on six occasions across 7 years. Multilevel modeling within an accelerated longitudinal design revealed that girls spent more time on housework than did boys but that housework time of both girls and boys increased from middle childhood to mid-adolescence and leveled off thereafter. In years when mothers were employed for more hours than usual, girls, but not boys, spent more time on housework than usual. Housework time was linked to more depressive symptoms (at a between-person level) and predicted lower school grades (at a within-person level) for youth with low familism values. Housework time also predicted more depressive symptoms (at a within-person level) for youth with high parent-youth conflict about housework. Findings highlight the gendered nature of housework allocation and the importance of considering both individual and contextual factors when examining youth daily activities.